2015
DOI: 10.5588/pha.14.0106
|View full text |Cite
|
Sign up to set email alerts
|

The development and implementation of a newborn medicine program in a resource-limited setting

Abstract: The reduction in global neonatal mortality rates remains a challenge. Internationally recognized protocols for hospital care of sick and small newborns are limited, although this specialized area lends itself to standardization. An interdisciplinary team including international and local clinical experts worked with the Rwandan Ministry of Health and Rwandan professional associations to develop and implement a neonatal care program in a rural Rwandan district hospital that was ultimately accepted as the nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 3 publications
(4 reference statements)
0
27
0
Order By: Relevance
“…Although the percentage of Rwandan women delivering in a health facility increased from 28% in 2005 to 69% in 2010 [ 10 ], evidence suggests numerous gaps in the quality of facility-based care during delivery and the early neonatal period [ 33 ]. Evidence-based policies and programs to improve neonatal care are underway, and this is an important area for future study [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the percentage of Rwandan women delivering in a health facility increased from 28% in 2005 to 69% in 2010 [ 10 ], evidence suggests numerous gaps in the quality of facility-based care during delivery and the early neonatal period [ 33 ]. Evidence-based policies and programs to improve neonatal care are underway, and this is an important area for future study [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Rwanda Ministry of Health (MOH) developed a national neonatal care protocol and standards in partnership with a number of organizations, including Partners In Health/Inshuti Mu Buzima (PIH/IMB) - an international non-profit organization committed to improving health services in impoverished communities - and specialists from Boston Children’s Hospital in Boston, USA. The neonatal care package was nationally adopted in 2012 with the goal of providing quality care to sick and preterm/low birth weight infants in rural district hospitals which lack specialist physicians [ 17 , 18 ]. The protocol was initially implemented and tested in the neonatal units of two rural PIH/IMB supported MOH district hospitals in 2010–2011.…”
Section: Introductionmentioning
confidence: 99%
“…Medical education reform is a continuous process whose primary goal is to realign curricula with the needs of the healthcare system of the society [ 21 ]. Examples of curricula review can be found in limited resource settings too for example Rwanda [ 22 ] and India [ 23 ]. In both countries there was successful development and implementation of a neonatal training program aimed at general practitioners and nurses on a background of needs assessment findings of poorly standardized care and wide variation in practices from place to place.…”
Section: Discussionmentioning
confidence: 99%